2023
DOI: 10.3389/fpls.2023.1199215
|View full text |Cite
|
Sign up to set email alerts
|

The synthesis of Paris saponin VII mainly occurs in leaves and is promoted by light intensity

Abstract: Unraveling the specific organs and tissues involved in saponin synthesis, as well as the light regulatory mechanisms, is crucial for improving the quality of artificially cultivated medicinal materials of Paris plants. Paris saponin VII (PS VII), a high-value active ingredient, is found in almost all organs of Paris plant species. In this study, we focused on Paris polyphylla var. yunnanensis (Franch.) Hand. - Mzt. (PPY) and found that PS VII synthesis predominantly occurs in leaves and is increased by high li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Organelles such as chloroplasts have finding. More recently, Wen et al (2023) analyzed by TEM the subcellular localization of saponins in Paris polyphylla leaves and showed that saponin are present in various cellular components, including membrane, chloroplasts, mitochondria and cell wall. They also demonstrated that the Paris saponin VII (the predominant Paris saponin in leaves and stems) is synthetized in mesophyll cells and then transported through vascular tissue to the rhizome for storage (Wen et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Organelles such as chloroplasts have finding. More recently, Wen et al (2023) analyzed by TEM the subcellular localization of saponins in Paris polyphylla leaves and showed that saponin are present in various cellular components, including membrane, chloroplasts, mitochondria and cell wall. They also demonstrated that the Paris saponin VII (the predominant Paris saponin in leaves and stems) is synthetized in mesophyll cells and then transported through vascular tissue to the rhizome for storage (Wen et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Wen et al (2023) analyzed by TEM the subcellular localization of saponins in Paris polyphylla leaves and showed that saponin are present in various cellular components, including membrane, chloroplasts, mitochondria and cell wall. They also demonstrated that the Paris saponin VII (the predominant Paris saponin in leaves and stems) is synthetized in mesophyll cells and then transported through vascular tissue to the rhizome for storage (Wen et al, 2023). With TEM analysis we found that leaf parenchyma cells' cytosolic compartment, vacuoles and nuclei of M. truncatula are devoid of saponin so these compartments and organelles can be ruled out as synthetic sites for saponins.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that the saponins contained in the leaves of P. polyphylla var. yunnanensis are similar to those in the rhizomes, such as polyphyllin II and polyphyllin VIII (Figure 1) [13], and it was even found that the synthesis of polyphyllin VII was mainly in the leaves [14]. Therefore, it is the focus of this study to find an economical and practical extraction method to improve the extraction efficiency of the medicinal components contained in the leaves of P. polyphylla var.…”
Section: Introductionmentioning
confidence: 88%